The influence of political party relationship patterns on people’s voting decisions ahead of the 2024 Elections - Nastain, M; Wulandari, Margareta; Faza Fariha, Naela; Lestari, Feni Indah; Pusphita Sari, Nurmala (Universitas Ahmad Dahlan, 2024)
In the modern political context, the pattern of political party relations is an important aspect that influences voter attitudes and preferences. This relates to a rational perspective, where the mechanism of the relationship between political parties and society is a symbiotic relationship of mutualism. This research aims to determine the real influence of the pattern of political party relations on people's voting decisions ahead of the 2024 elections. In the upcoming 2024 elections, the General Elections Commission (KPU) determines 17 political parties as participants. With a large number of political parties, the reality of the relationship between political parties and voters becomes interesting. This study uses a quantitative approach by taking populations from two islands in Indonesia, namely Sumatra and all of Java. The research method used is non-proportional random sampling. Respondents came from 9 provinces in Indonesia with a total of 225 respondents. Variable X in this study is the relationship between political parties and the community and variable Y is the decision to vote. The results of the regression test obtained were Significance F = 0.000 <alpha (0.05) so it can be concluded that variable X has an influence on variable Y. Furthermore, based on the Multiple R value = 0.454, the correlation between the two variables is included in the medium category.